Polityka cen transferowych w grupie kapitałowej na przykładzie koncernu Bosch - Jaruga, Alicja (Transfer pricing policy in Bosch corporation, 2008)
Transfer prices of goods and raw materials are calculated according to cost plus and price of resale method. According to this policy transfer prices depend on direct and indirect costs or incomes from sales outside of group. Low prices of goods produced and distributed by Bosch group are the reason of Bosch Uktady Hamulcowe loss in 2007. It is necessary to underline that, from economic point of view - in a limited period - sales which do not cover all production costs, but cover only variable costs, are more advantageous than to give up production. An additional reason to continue non profitable production is aspiration of Bosch group to be the main player in the market.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 15, s. 105-112